2020
DOI: 10.3390/cancers12082173
|View full text |Cite
|
Sign up to set email alerts
|

The Role of RNA and DNA Aptamers in Glioblastoma Diagnosis and Therapy: A Systematic Review of the Literature

Abstract: Glioblastoma (GBM) is the most lethal primary brain tumor of the central nervous system in adults. Despite advances in surgical and medical neuro-oncology, the median survival is about 15 months. For this reason, initial diagnosis, prognosis, and targeted therapy of GBM represent very attractive areas of study. Aptamers are short three-dimensional structures of single-stranded nucleic acids (RNA or DNA), identified by an in vitro process, named systematic evolution of ligands by exponential enrichment (SELEX),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 67 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…By generation of ROS in the glioma cell line U-87 M, salinomycin caused endoplasmic reticulum stressmediated autophagy and apoptosis [116]. The exercise-induced myokine irisine suppressed tumor proliferation, invasion, and growth of GBM cells by G 2 /M cell [3] cycle arrest and by increasing the levels of p21 [117]. It was shown that sulforaphane (SFN), which is obtained from cruciferous vegetables, induced apoptosis in tumor tissues.…”
Section: Other Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…By generation of ROS in the glioma cell line U-87 M, salinomycin caused endoplasmic reticulum stressmediated autophagy and apoptosis [116]. The exercise-induced myokine irisine suppressed tumor proliferation, invasion, and growth of GBM cells by G 2 /M cell [3] cycle arrest and by increasing the levels of p21 [117]. It was shown that sulforaphane (SFN), which is obtained from cruciferous vegetables, induced apoptosis in tumor tissues.…”
Section: Other Drugsmentioning
confidence: 99%
“…The induction of cell apoptosis by this SFN-Cys involves the long-term activation of ERK1/2-and ERK1/2-mediated signaling pathways such as the activation of caspase 3 and proteins associated with apoptosis. Macromolecules such as DNA-or RNA-aptamers [3,119], antibodies [120], metal core nanoparticles (NPs), peptide nanoparticles [121][122][123], liposomes (ImmuLipCP) [124], CAR T cells [125], and CRISPR/Cas tools [126] are gradually included in a number of therapeutic drugs or theranostics for glioblastoma in in vivo or in vitro experiments.…”
Section: Other Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…and have boosted the resurgence of RNAi technology ( Bobbin and Rossi, 2016 ). In the 2016 World Health Organization’s classification of tumors of the central nervous system, glioblastoma (GBM) was categorised as grade IV astrocytoma, which is a commonly seen lethal brain tumor, and many aptamers have already been tested as therapeutic agents in GBM ( Watts and Corey, 2012 ; Louis et al, 2016 ; Nuzzo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the urgent need for finding the optimal and targeted treatment option for GBM patients [29,30], and given the proven power of diffusion MRI techniques for applications such as preoperative grading, postoperative assessment of glial tumours and differentiation of GBM from other tumours types (such as brain metastasis or PCNSL [31][32][33]), several studied investigated the association of diffusion MRI metrics with survival outcomes in patients with GBM. Some of these were performed on newly diagnosed GBM patients, while others on recurrent GBM patients.…”
Section: Introductionmentioning
confidence: 99%